HUBUNGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA KEUANGAN DAN HARGA SAHAM PADA PERUSAHAAN LQ45 - Hamdani, Mailani (Jurnal Organisasi Dan Manajemen, 2014)
This study aimed to analyze the relationship between the disclosure of Coporate Social Responsibility (CSR) and financial performance stock price in the LQ45 company. This study used the annual reports of LQ45 company in period FebJul 2012 for the data. The variable were based on the standard CSR disclosure Global Reporting Initiatives(GRI), the financial performance reflected by the current ratio, return on assets (ROA), return on equity (ROE), debt to equity/CAR, as well as stock prices reflected by the return stock. The results were Coporate Social Responsibility (CSR) disclosure in annual reports related significantly to financial performance, it means that better Coporate Social Responsibility (CSR) disclosure in annual report will result to better financial performance. Coporate Social Responsibility (CSR) disclosure in in the annual report related significantly to the stock price, it means that better Coporate Social Responsibility (CSR) disclosure in annual reports will result in higher stock price. And the result for this research is the financial performance related significantly to stock price of a company, it means that the better financial performance of a company will increase the stock price in the company.   Penelitian ini bertujuan untuk menganalisis hubungan antara pengungkapan tanggung jawab Coporate Social Responsibility (CSR) dan harga saham kinerja keuangan di perusahaan LQ45 . Penulis menggunakan laporan tahunan perusahaan LQ45 pada periode Februari-Juli 2012 untuk data. Variabel didasarkan pada pengungkapan CSR standar Global Reporting Initiatives (GRI), kinerja keuangan tercermin dari rasio lancar, return on assets (ROA), return on equity (ROE), debt to equity / CAR, serta harga saham fre pantulan oleh return saham. Hasilnya menunjukkan Coporate Social Responsibility (CSR) pengungkapan dalam laporan tahunan terkait signifikan terhadap kinerja keuangan, itu berarti bahwa memperluas Coporate Social Responsibility (CSR) pengungkapan dalam laporan tahunan kinerja keuangan yang lebih baik. Coporate Social Responsibility (CSR) pengungkapan di dalam laporan tahunan terkait signifikan terhadap harga saham, itu berarti bahwa memperluas Coporate Social Responsibility (CSR) pengungkapan dalam laporan tahunan higer untuk itu harga saham. Dan hasil penelitian ini adalah kinerja finansial yang berhubungan signifikan terhadap harga saham perusahaan, itu berarti bahwa semakin baik kinerja keuangan perusahaan akan meningkatkan harga saham di perusahaan.